Synthesis of Azetidine Nitrones by Double Methylene Incorporation into Nitrile Oxides Using Diazomethane - Iwamoto, Ryo; Suga, Takuya; Soeta, Takahiro; Ukaji, Yutaka (Synlett, 2025)
A novel method for preparing 4-membered azetidine nitrones, starting from isolable nitrile oxides, has been developed. The reaction of diazomethane with the bulky nitrile oxides proceeds via double nucleophilic incorporation of the methylene moiety to produce 4-membered cyclic nitrones in yields up to 74%. A reaction pathway involving the formation of a strained azirine N-oxide intermediate is discussed.
Keywords: Nitrile oxide; Diazomethane; Double methylene incorporation; Azetidine nitrone; Azirine N-oxide